Exploring Baudrillard’ Simulation and Simulacra in Wilde’s The Picture of Dorian Gray and The Importance of Being Earnest - Sade-dine, Youssera Belkisse; Selt ,Djihad (Faculty of Letters and Foreign Languages Department of English, 2018)
This dissertation offers a study on Baudrillard’s theory of ‘Simulation and Simulacra’ in Oscar Wilde’s novel The Picture of Dorian Gray and his well- known play The Importance of Being Earnest. In the former, Wilde attempts to integrate his thoughts and beliefs about the role of art in society. In doing so, he provided an identical painting of the protagonist in his plot. This painting did not just imitate the main character Dorian physically but also on the spiritual level. The painting copied the protagonist so much that it became mistaken to be the real Dorian Gray. In the latter play, Wilde also inserts the idea of copies and reproduction of the real. He tends to create fake characters that resemble the real ones for the sake of specific aims that are explained in the play. In the end, he realizes these unreal characters and gives them more attention than the real ones. In both of his works, Wilde embodies the concept studied by Jean Baudrillard of hyperreality. In both of his works, the Irish author tries to comment on the issue of originality and authenticity in the modern world. This study aims to examine the characters of both of the novel and the play along with the different elements that represent hyperreality and to see to which extent Wilde’s writings correspond to Baudrillard’s theory